Benchmarking as an Instrument of Increase in Efficiency of Enterprise's Activity ("Journal "U". Economy. Management. Finance.", 2017)
This article is devoted to the analysis of a role of benchmarking in enterprise's activities. The work considers concepts, purposes, tasks and functions of benchmarking, its role and influence on efficiency of enterprise's activities. Topicality of this subject doesn't raise doubts as the benchmarking is one of the main instruments of increase in efficiency of enterprises.
Keywords: benchmarking; marketing communications